Using Water Energy for Electrical Energy Conservation by Building of Micro hydroelectric Generators on The Water Pipelines That Depend on The Difference in Elevation - Gatte, Engineer Mohammed Taih; Kadhim, Engineer Rasim Azeez; Rasheed, Engineer Farhan Leftah (Iraqi Journal for Electrical and Electronic Engineering, 2011)
In this research we study the elevations of cities and the water resources specially at the dams reservoirs and the distance between them(dams & cities), we use the Google Earth program to determine these elevations and calculate the difference between the average level (elevation) of water at the dam and the average level of cities, which we want to supply it by water, in order to save electrical power by using the energy of supplied water through pipe line from dams to the cities, the pressure of supplied water must be calculated from the difference in elevations(head). The saving of energy can be achieved by two ways. The first is the energy saving by reduce the consumed power in the pumping water from river, which is used for different purposes. The second is the hydroelectric power generated by establishing a micro hydroelectric generator on the pipe line of the water supplied.